Numerical study on hybrid metallic sandwich structures subjected to air burst - Solomon Abebe Derseh; Tesfaye Alemu Mohammed; Girum Urgessa (SN Applied Sciences, 2023)
Abstract This study presents a numerical investigation on the use of previously unexplored hybrid sandwich protective structural configurations with aim to resist airblast loading. A honeycomb, corrugated sheet, and woven interlaced core configurations are used to develop the hybrid system. An experimental result reported in the previous literature is used for validation of the finite element analysis models using Abaqus/Explicit finite element software with a conventional weapon blast related parametric codes. Then an extended numerical study is conducted further on various hybrid sandwich inner core topologies for maximizing protection against an air blast induced shock wave. The study demonstrated that a protective system, combining square honeycomb metallic cores with X-shaped corrugated sheets and fortified against in-plane compression and buckling, showed excellent shielding capabilities against airblast loading. This configuration also exhibited the highest energy dissipation, the least effective plastic strain, minimal back sheet displacement, and a favorable damage profile.